2011
DOI: 10.1089/sur.2009.081
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Treatment of Pyomyoma in the Postpartum Period

Abstract: Therapy via drainage and lavage of pyomyoma is a viable option to preserve patient fertility. In the absence of a proper response to this treatment, total abdominal hysterectomy is the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Traditional surgical approaches to treatment of pyomyoma have been hysterectomy and myomectomy, both cases we reported showed complete resolution of symptoms after total abdominal hysterectomy was performed. More recently other approaches have been introduced such as CT guided drainage [23] and Pinto et al [7] discussed laparoscopic approach for drainage and lavage of a perforated pyomyoma. These are also viable approaches to patients desiring to avoid irreversible sterility associated with Hysterectomy and a less invasive alternative to myomectomy and hysterectomy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional surgical approaches to treatment of pyomyoma have been hysterectomy and myomectomy, both cases we reported showed complete resolution of symptoms after total abdominal hysterectomy was performed. More recently other approaches have been introduced such as CT guided drainage [23] and Pinto et al [7] discussed laparoscopic approach for drainage and lavage of a perforated pyomyoma. These are also viable approaches to patients desiring to avoid irreversible sterility associated with Hysterectomy and a less invasive alternative to myomectomy and hysterectomy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Laubach et al 9 have recently shown the use of CT-guided drainage and lavage of pyomyoma related to pregnancy in two out of three cases successfully. They suggest that image-guided drainage is a safer, minimally invasive option for these patients who can be critically ill and septic, exposing them to less risks of extensive surgery and also preserving fertility 9.…”
Section: Discussionmentioning
confidence: 98%
“…They suggest that image-guided drainage is a safer, minimally invasive option for these patients who can be critically ill and septic, exposing them to less risks of extensive surgery and also preserving fertility 9. In the absence of complete recovery, however, the option of TAH still remains.…”
Section: Discussionmentioning
confidence: 99%
“…As for pyomyoma linked to pregnancy, 16 cases (including this case) have been reported since 1945 after the antibiotic era. The cases are shown chronologically in Table 1 4–16 . Most cases exhibited an interval of days to weeks between delivery or abortion and onset of symptoms, suggesting that most pyomyomas developed insidiously resulting from extension of endometritis caused by intrauterine manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…The cases are shown chronologically in Table 1. [4][5][6][7][8][9][10][11][12][13][14][15][16] Most cases exhibited an interval of days to weeks between delivery or abortion and onset of symptoms, suggesting that most pyomyomas developed insidiously resulting from extension of endometritis caused by intrauterine manipulation. Only four cases were involved in pyomyoma during pregnancy, and the current case alone continued to term delivery.…”
Section: Discussionmentioning
confidence: 99%